Cloud-Based Learning Platforms and Their Impact on English Writing Skills in Rural Schools - Olivia Green; Thomas Mitchell; Amine Ali (International Journal of Language and Ubiquitous Learning, 2025)
Background. In rural Indonesian schools, where access to qualified English teachers and adequate learning resources is often limited, these platforms provide a potential solution to reduce the urban rural education gap, particularly in the development of writing skills. Purpose. This study aimed to investigate the impact of cloud-based learning platforms on students’ English writing skills in rural secondary schools. It focused on examining how digital collaboration, feedback mechanisms, and self-paced learning influence writing performance and learner engagement. Method. A mixed-method research design was employed involving 100 students from three rural secondary schools in Indonesia. Participants took part in a 10-week instructional intervention using cloud-based platforms, namely Google Classroom and Microsoft OneNote. Results. The findings indicated a significant improvement in students’ English writing performance after the intervention (p < .05), particularly in text organization, vocabulary use, and grammatical accuracy. Qualitative analysis revealed that cloud-based platforms increased learner motivation, promoted peer collaboration, and enabled timely and effective teacher feedback despite existing infrastructural limitations. Conclusion. The study concludes that cloud-based learning platforms effectively support the development of English writing skills in rural educational contexts.